PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN ( Studi pada Perusahaan LQ 45 yang Terdaftar Di BEI Periode 2013 - 2017 ) - Fitri Wardihana, 15.05.52.0155; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the Effect of Profitability, Leverage, Company Size, and Dividend Policy on Company Values in LQ 45 Companies listed on the Indonesia Stock Exchange in the period 2013 - 2017. The Company Value is a balance or comparison between Price Per Share Sheet and Book Value Per Sheet Stock. The population in this study were companies listed on the LQ-45 index during the period 2013-2017. The sample selection technique uses a purposive sample and obtained 24 companies with a period of 5 years so that the 120 data studied are obtained, and processed with the SPSS application. Based on the results of data processing, it was found that Profitability, Leverage and Dividend Policy affect the value of the company. While Company Size has a negative and significant effect on Company Value. The results of the coefficient of determination test (R2) are 0.723. These results indicate that 72.30% is influenced by profitability, leverage, company size, and dividend policy while the remaining 27.70% is influenced by other variables.